A comparative study of breast lesions using the IAC Yokohama System for reporting breast cytopathology against histopathological biopsy - Chandrakala Joshi; Ruchi Varma; Shruti Tiwari Pande (MGM Journal of Medical Sciences)
Background: Breast lumps pose a significant health concern globally, contributing to both illness and death. The International Academy of Cytology (IAC) Yokohama system has established a uniform method for reporting breast cytology, categorizing it into five groups: inadequate, benign, atypical, suspicious, and malignant. Aims and Objectives: This study primarily aimed to evaluate breast lesions using the IAC Yokohama System and compare the results with those of corresponding histopathological biopsies. Additionally, the study aimed to analyze the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy of breast fine-needle aspiration cytology (FNAC) and determine the risk of malignancy associated with each category. Materials and Methods: In this study, 92 cases were analyzed and categorized according to the IAC Yokohama System. Sensitivity, specificity, PPV, NPV, diagnostic accuracy, and risk of malignancy were determined based on histopathological diagnosis, which was considered the reference standard. Results: Among the 92 breast FNACs, the risk of malignancy for the categories insufficient, benign, atypical, suspicious, and malignant were 0%, 0%, 18.75%, 100%, and 100%, respectively. The highest sensitivity (100%) was achieved when considering atypical, suspicious, and malignant cases as positive results. The specificity was highest (100%) when only malignant or both malignant and suspicious cases were considered positive results. The highest diagnostic accuracy (95.65%) was observed when including malignant and suspicious cases as positive results. Conclusion: Implementing the IAC Yokohama System for reporting breast cytopathology through structured reporting will enhance the quality, clarity, and reproducibility of reports among pathologists and clinicians, which would result in enhanced patient care and management.